Cultural Soft Power of China and Japan: Competition and Interaction in the Digital Era / Культурная «мягкая сила» Китая и Японии: конкуренция и взаимодействие в цифровую эпоху - GEORGII D. PAKSIUTOV / ПАКСЮТОВ Г.Д. (Наука телевидения)
The article explores the resources, conceptualization, and pros-pects of China’s soft power strategy, examining its interactions with the US, its largest political competitor, and Japan, another East Asian soft power giant. Special focus is placed on the challenges and opportunities arising from the digitalization of culture. It is highlighted that the digital creative industries offer significant potential for disseminating Chinese and Japanese narratives, showcasing a significant synergy between the creative sectors of these two countries. Additionally, the article notes that infrastructure invest-ments is an important part of the soft power strategies of both China and Japan, which is particularly significant given the pivotal role data and infor-mation technologies play in the success of content industries today. Draw-ing distinctions in how soft power is perceived in China and the US, it is sug-gested that China’s strategy stems from a unique understanding of culture that prioritizes community and blurs the sharp binary distinctions between private and public, tangible and intangible aspects. The argument is made that this cultural approach, combined with the allure of Chinese education and economic models, positions China’s strategy for success amidst the digital revolution and the advancement of artificial intelligence, especially resonating in Global South countries. With AI advancements potentially threatening to reduce numerous jobs, the narratives of economic empow-erment championed by China become increasingly appealing, especially in the Global South.